[San Quentin Prison Report:] Educational, Library, and Religious Activities for the biennium ending June 30, 1928 (1928)
Detailed report of the activities at San Quentin prison including: facilities improvements, educational activity, the completion of the women's prison, road camps, instructional classes, the quality of work completed by the students, summary of education of inmates prior to incarceration, recommendations to improve, library book circulation, religious activity, schedule of religious services offered.